Slow freezing cryopreservation of Korean bovine blastocysts with an additional sucrose pre-equilibration step - Jung, Seungki; Sul, Hyeonseok; Oh, Dongjin; Jung, Yeon-Gil; Lee, Joohyeong; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2024)
Introduction: Embryo cryopreservation is a valuable technique used for preserving genetic resources for long periods. However, the survival rate of embryos is dependent on the method used. Therefore, in this study, we evaluated the efficiency of slow freezing method but with an additional dehydration step prior to freezing to overcome the formation of ice crystals. Methods: Oocytes collected from the ovaries of native Korean cattle subjected to in vitro fertilization were cultured for 7 d until the formation of expanded blastocysts. Before freezing, the blastocysts were placed in four preequilibration media: a control medium with no addition of sucrose, and three experimental media with the addition of 0.1M, 0.25M, and 0.5M sucrose, respectively. Then, the pre-equilibrated embryos were frozen. Embryo survival and hatching rates were evaluated morphologically at 24, 48, and 72 h after thawing. Immunofluorescence staining, terminal deoxynucleotidyl transferasemediated dUTP nick end labeling (TUNEL) assay, and gene expression analysis of the re-expanded blastocytes were examined 24 h after freeze-thawing. Results: The survival rate was significantly higher in the 0.1 M group than in the control group (p < 0.05), and the hatching rate at 72 h was significantly higher in the 0.25 and 0.5 M groups than in the control group (p < 0.05). TUNELpositive cells were significantly lower in the 0.25 M group than in the control group (12.5 ± 0.9 vs. 8.3 ± 0.8; p < 0.05). The gene expression of BCL2 associated X, heat shock protein 70 kDa, and aquaporin 3 in the 0.25 M group was significantly lower than that in the control group (p < 0.05). Conclusion: Our study revealed that treatment with 0.25 M sucrose before slow freezing improved the viability of bovine embryos after freeze-thawing.